Inovasi Perpustakaan dalam Mendukung Program E-Learning di masa Pandemi Covid-19 - Mustar, Maniso (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2021)
Background: The Covid-19 pandemic has had various impacts on society. The impact on the world of education is one of them. The community is required to follow changes in learning patterns from face-to-face to long-distance which is often called e-learning. For this reason, various parties are needed to support this learning process, one of which is a library with the aim of supporting the learning process of the community in the midst of pandemic.Methodology: This research uses descriptive research method. For data collection and analysis methods using literature studies from various references.Results and Discussion: Raising awareness of the importance of education during a pandemic to the public, distance learning is a need that must be met with synergy of education providers, communities, governments and libraries. Innovation in circulation services, database services and e-resources, managing online library events, compiling credible information sources and coordinating among librarians are expected to support e-learning programs in Indonesia.Conclusion: This study shows that e-learning is very much needed by society in current and future conditions. The education system can be implemented practically, efficiently and facilitates community learning. Library innovation to support e-learning is also very much needed to support the community learning process in the midst of a pandemic.